Mongolia : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
This Joint Staff Assessment assesses the Economic Growth Support and Poverty Reduction Strategy (EGSPRS), which is the first full poverty reduction strategy paper (PRSP) prepared by the government of Mongolia. The EGSPRS builds on the strategy articulated in the interim report (I-PRSP) presented to the Boards of the International Development Association (IDA) and the International Monetary Fund (IMF). It provides an adequate framework for implementing the government's development agenda and highlights several weaknesses and challenges associated with its successful implementation.